PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN CARDSORT BERBASIS WORDWALL TERHADAP KEAKTIFAN SISWA DALAM PEMBELAJARAN IPS DI KELAS UNGGULAN SMP ASA CENDEKIA SEDATI - Anggi Wayuningtyas; Sukma Perdana Prasetya; Dian Ayu Larasati; Riyadi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Student activeness is an important component of Social Studies learning because students are expected not only to understand concepts, but also to ask questions, discuss, express opinions, and participate in learning activities. In class VII A, the outstanding class of SMP Asa Cendekia Sedati, student involvement was still uneven, particularly in asking questions, responding to questions, and expressing opinions. This study aimed to determine the effect of using Wordwall-based cardsort learning media on student activeness and to determine the magnitude of the effect. The study employed a quantitative approach with a one-shot case study design. The population and sample consisted of 28 students selected through saturated sampling. Data on the learning media variable were collected using a 25-item closed Likert-scale questionnaire, while student activeness data were obtained through an observation sheet. The questionnaire was valid and reliable, with a Cronbach’s Alpha coefficient of 0.886. Data were analyzed using prerequisite tests and spline regression. The results showed that the spline regression model was significant, with an F value of 38.641 and a significance value of 0.000 < 0.05. The R Square value of 0.756 indicates that Wordwall-based cardsort media explained 75.6% of the variation in student activeness, while the remaining 24.4% was explained by other factors. Observation results showed an average student activeness score of 90%, categorized as very good. Therefore, the use of Wordwall-based cardsort learning media had a significant and high contribution to student activeness in Social Studies learning.